Rapamycin inhibits proliferation and migration of hepatoma cells in vitro - Shirouzu, Yasumasa; Ryschich, Eduard; Salnikova, Olga; Kerkadze, Vachtang; Schmidt, Jan; Engelmann, Guido (Journal of surgical research, 2010)
BACKGROUND: Systemic immunosuppression represents the major factor for cancer recurrence after orthotopic liver transplantation for hepatocellular carcinoma (HCC). Rapamycin is an immunosuppressant with unique antitumoral properties. Although rapamycin has been successfully used in HCC patients after liver transplantation, the detailed mechanisms of rapamycin action on tumor cells are poorly understood. - METHODS: Two HCC cell lines (PLC5 and HuH7) were used to evaluate the effect of rapamycin. Tumor cell proliferation was analyzed using cell counting and BrdU incorporation assay. Expression of phosphorylated Akt was studied using enzyme linked immunosorbent assay. Digital time-lapse microscopy was utilized to measure tumor cell migration in vitro. - RESULTS: Rapamycin induced a strongly dose-dependent inhibition of tumor cell proliferation in both HCC cell lines. Additionally, rapamycin inhibited activation of Akt phosphorylation and tumor cell migration after prolonged treatment. - CONCLUSIONS: Rapamycin suppresses tumor progression due to inhibition of phosphorylated Akt, cell proliferation, and migration. The data of the present study strengthen clinical implications of rapamycin after liver transplantation with HCC.
Gesehen am 18.07.2023